Rethinking management information systems : an interdisciplinary perspective - Currie, Wendy, 1960-; Galliers, Robert, 1947- (Oxford University Press, 1999)
This book examines influential ideas within Management Information Systems (MIS). Leading international contributors summarize key topics and explore a variety of issues currently being discussed in the field. They re-visit influential ideas such as socio-technical theory, systems thinking, and structuration theory and demonstrate their relevance to newer ideas such as re-engineering, hybrid management, knowledge workers, and outsourcing. In locating MIS within an interdisciplinarycontext, particularly in the light of rapid technological changes, this book will form the link between past and f.